Cost-Effectiveness Analysis Of Biomarker-Based And Risk-Based Screening In Early Detection Of Preeclampsia: Systematic Review - Aurellia Saraswati Winahyu Naiaputri (International Journal of Health Engineering and Technology, 2026)
Preeclampsia is one of the leading causes of maternal morbidity and mortality, especially in developing countries. Evaluation of the cost-effectiveness of first-trimester screening is essential to ensure accurate and efficient interventions. The objective of this review is to examine and compare the cost-effectiveness between biomarker-based preeclampsia screening and maternal risk-based screening in the first trimester of pregnancy. This study used a systematic review method based on the PRISMA guidelines. Articles searched through PubMed and ScienceDirect with a range of 2020–2025. Quality assessment using the CHEERS Checklist. Five studies were included in this review. All studies show that first-trimester preeclampsia screening is a cost-effective, even cost-saving strategy, especially when combined with early aspirin. Biomarker-based screening and risk algorithms are more cost-efficient than conventional screening. These results can be the basis for the formulation of maternal health policies in Indonesia. Preeclampsia, first trimester screening, cost-effectiveness, biomarkers.